OC-017 A comparison of non-invasive fibrosis scoring systems in patients with non-alcoholic fatty liver disease. (23rd September 2015) - McPherson, S; Stewart, S; Henderson, E; Burt, A; Day, C
Abstract : Introduction: Non-alcoholic fatty liver disease (NAFLD) affects approximately 30% of the population, with 3% having non-alcoholic steatohepatitis (NASH), which may progress to cirrhosis and liver failure. Accurate evaluation of liver fibrosis is important to identify patients who may develop complications. Liver biopsy is limited by its invasive nature. Therefore, several non-invasive strategies derived from simple clinical and laboratory parameters have been developed to identify patients with advanced fibrosis. The aim of this study was to compare the diagnostic performance of several non-invasive tests in patients with biopsy-proven NAFLD. Methods: Patients who were reviewed in the Freeman Hospital liver clinic from 2003-2009 were included. Liver biopsies were assessed using the Kleiner score. The AST/ALT ratio, AST to platelet ratio index (APRI), BARD, FIB-4 and NAFLD fibrosis scores were calculated from blood tests taken within 6 months of liver biopsy. Results: 145 patients (82 male (61%), mean age 51±12 years) were included. The mean BMI was 34.8±5 and 73 subjects (50%) had diabetes. 93 patients (64%) had NASH and 27 (19%) had advanced fibrosis (F3-4). The FIB-4 score had the best diagnostic accuracy for advanced fibrosis (AUROC 0.86), followed by AST/ALT ratio (AUROC 0.83), NAFLD fibrosis score (AUROC 0.81), BARD score (AUROC 0.77) and APRI (AUROC 0.67). Abstract OC-017 shows NPVs and PPVs for each test using specific cut-offs, along with the proportions of patients who could avoid liver biopsy by using each score. Conclusion: The AST/ALT ratio, BARD, FIB-4 and NAFLD scores have good accuracy for excluding advanced fibrosis. Use of the ALT/AST ratio or FIB-4 score potentially allows liver biopsy to be avoided in a high proportion of patients with reasonable accuracy, meaning liver biopsy may be used in a more directed manner.